2019
DOI: 10.1101/531442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacteriophage resistance alters antibiotic mediated intestinal expansion of enterococci

Abstract: 27Enterococcus faecalis is a human intestinal pathobiont with intrinsic and acquired resistance to 28 many antibiotics, including vancomycin. Nature provides a diverse and virtually untapped repertoire of 29 bacterial viruses, or bacteriophages (phages), that could be harnessed to combat multi-drug resistant 30 enterococcal infections. Bacterial phage resistance represents a potential barrier to the implementation 31 of phage therapy, emphasizing the importance of investigating the molecular mechanisms underly… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 46 publications
0
22
1
Order By: Relevance
“…TnSeq identified numerous E. faecalis genes that govern VPE25 susceptibility. Mutations in epa variable genes conferred VPE25 resistance by preventing phage adsorption, similar to other E. faecalis phages (23, 3537). We discovered that phage infection of mismatch repair gene mutants results in the emergence of phage adsorption deficiencies, thus the mismatch repair system likely fails to correct DNA damage of epa genes during phage infection.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…TnSeq identified numerous E. faecalis genes that govern VPE25 susceptibility. Mutations in epa variable genes conferred VPE25 resistance by preventing phage adsorption, similar to other E. faecalis phages (23, 3537). We discovered that phage infection of mismatch repair gene mutants results in the emergence of phage adsorption deficiencies, thus the mismatch repair system likely fails to correct DNA damage of epa genes during phage infection.…”
Section: Discussionmentioning
confidence: 62%
“…epa genes encode proteins involved in the formation of a cell surface-associated rhamno-polysaccharide (34). We and others have previously demonstrated that enterococcal phages unrelated to VPE25 utilize Epa to adsorb and infect E. faecalis (23, 3537). Initial work from our group showed that mutation of the VPE25 receptor Pip EF prevented VPE25 DNA entry into E. faecalis V583, yet phages could still adsorb to receptor mutants (32), suggesting that the factors that promote phage infection via surface adsorption remained to be identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations